Comparison of Different Additively Manufactured Ti6Al4V Scaffold Designs - Singh, Sachin; Saini, J. S.; Rojdeep Singh (Defence Science Journal, 2024)
The cellular structures, repeated array of unit cells in all the three directions, are light weighted, resist bending and buckling due to their intricate structural organization. These structures allow tailoring the mechanical properties of the biomaterial structure near to that of the surrounding bones which helps in reduction of the stress shielding effect. Over the years, various fabrication processes were introduced and evolved for producing cellular (porous) structures with unique mechanical properties, biocompatibility, corrosion rate, degradation rate, etc. In the current work, CAD models of titanium scaffolds has been designed and later manufactured by 3D..........